An exact algorithm to solve a cloud service bilevel problem. - López Vear, Lilian (2018)
Technology is a word used to describe the way humans are changing their lives by materializing and joining knowledge. Moreover, despite many people believe that technology has already changed generations and we are no longer a race that could survive without it, [7] showing significant ethical and social consequences . It is also proved that because all this materialization and join of different scientific aspects, is that we have reached a point where we have touched everything around us. We had been able to improve life quality, health, the way we understand our surroundings, facilitated traveling, and our most important, the fact that we can communicate no matter where we are. Despite technological advances entirely run our lives, when we talk about this topic, all that comes to our mind is one specific technological promoter: computers. And it is not something to be impressed, because since their appearance, they have impulsed all advances and scientific branches in almost all the fields. In the past 80 years, with the creation of modern computers and the invention of the internet, life as our forefathers knew it has been rapidly and continuously changing [19]. Being surrounded by this technology and the aim to improve work, communication, and life, also make us focus our attention on the future and the new challenges that arise for the operational research field, which emerged from a military context as a way of analyzing and solving specific real based problems. Operational Research with the use of mathematical logic and methods followed by a series of defined steps and based on their specific purpose can find or approach the best possible solution for a certain decision maker [20]. Operational Research is also evolving, and day by day, finding better ways to approach an optimal solution for each proposed problem. Moreover in operational research and focusing on this exciting information technology field, we get to the center of our study: Cloud Computing.